Exploring the Phytochemical Properties and Therapeutic Potential of Hibiscus sabdariffa Linn. and Stevia rebaudiana Bert. - Anjabtsawa, Daffa; Febriyanti, Raden Maya; Diantini, Ajeng (Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, 2024)
Indonesian people have used medicinal plants for ages to cure various diseases. Traditional medicinal plants offer a variety of health benefits and can be an excellent alternative to prevent various diseases. Herbal tea-based treatment is low-calorie and is good for health with many benefits. Rosella (Hibiscus sabdariffa Linn.) and Stevia (Stevia rebaudiana Bert.) plants are the main composition of herbal tea. They contain various secondary metabolite compounds that play a role in pharmacological activity like alkaloids, flavonoids, phenols, glycosides, steroids, tannins, coumarins, saponins, anthraquinones, and others. This review aims to collect the latest scientific information regarding the possible pharmacological activities of Rosella and Stevia plants. These plants have antioxidative, antibacterial, antidiabetic, antihypertensive, anticancer, antihyperlipidemia, anti-obesity, hepatoprotective, anti-inflammatory, and antiprotozoal potential. PubMed, Scopus, Cochrane, Google Scholar, ScienceDirect, and EBSCO were used to obtain literature published from 2017 to 2023. The study concludes that Rosella (Hibiscus sabdariffa Linn.) and Stevia (Stevia rebaudiana Bert.) plants have potential in the development of traditional medicinal plants with many benefits contained in them.